Estimation and comparison of serum lipid profile of women with pregnancy induced hypertension and normal pregnancy - Dev, Kapil; Sood, Rajeev; Sharma, Aanya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Hypertensive disorders during pregnancy are the most common medical complication seen during pregnancy, affecting around 5-10% of all pregnancies. Raised blood pressure in pregnancy is the major cause of fetomaternal morbidity and mortality. The most important feature in preeclampsia is hypertension which is supposed to be due to vasospastic phenomenon in kidney, uterus, placenta and brain. Altered lipid synthesis leading to decrease in PGI2:TXA2 ratio is also supposed to be an important way of pathogenesis in pregnancy induced hypertension. Methods: This one-year prospective case control study total 200 pregnant women attending antenatal care and admitted in eclampsia ward fulfiling the inclusion criteria were studied. Serum lipid profile was estimated by semiautomatic analyzers. Statistical analysis of data was done by student’s t-test and p-value. Results: Mean total cholesterol in pregnancy induced hypertension was 278.5±52.52 mg/dl and normal pregnancy was 245.47±20.075 mg/dl. Mean triglycerides in pregnancy induced hypertension was 249.88±92.575 mg/dl and normal pregnancy was 206.89±46.345 mg/dl. Mean HDL in pregnancy induced hypertension was 43.69±4.135 mg/dl and normal pregnancy was 49.9±6.501 mg/dl. Mean LDL in pregnancy induced hypertension was 174.43±39.083 mg/ dl and normal pregnancy was 151.22±19.92 mg/dl. Mean VLDL in pregnancy induced hypertension was 46.885±15.143 mg/dl and in normal pregnancy was 40.964±9.061 mg/dl, total cholesterol, low density lipoprotein, very low density lipoprotein, triglycerides were increased in pregnancy induced hypertension when compared to normal pregnancy, which is statistically significant. Conclusions: We concluded that the Patient who developed pre-eclampsia have abnormal lipid profile. This abnormal lipid profile is responsible for endothelial dysfunction. This endothelial dysfunction may play a key role the pathophysiology of pre-eclampsia. Early detection of these parameters may help patient by preventing complications and is going to aid in better management of pre-eclampsia.